PENGARUH EFEKTIVITAS IKLAN PESAING, ATRIBUT PRODUK, DAN PERILAKU MENCARI VARIASI TERHADAP PERILAKU PERPINDAHAN MEREK PRODUK INDOMIE - Hidayatullah, Syamsul; Astogini, Dwiwiyati; Sumarsono, Sumarsono (Faculty of Economics and Business Universitas Jenderal Soedirman, 2016)
The research entitled “effect of competitor advertisement effectiveness, product attribute, and variety seeking behavior to brand switching behavior of Indomie. The aim of this research is to analyze the effect of competitor advertisement effectiveness, product attribute, and variety seeking behavior to brand switching behavior of Indomie to other brand. Data collection method use questionnaire with a sample 100 respondents from economics and business faculty of Jenderal Soedirman university students who have switched from Indomie to other instant noodle brand. The data is analyzed by using multiple linier regression, meanwhile the significance level use partial test (t test).The result shows that competitor advertisement effectiveness, product attribute, and variety seeking behavior have positive significant effect to brand switching behavior of Indomie. Based on this research, managers are recommended to increase the advertising frequency, increase the quality of product, do endorsement, expand the taste variety, and also give innovation to every detail of product or pricing in order to minimalize brand switching behavior of consumer.